Ultrasound Instead of X-Ray to Diagnose Neonatal Fractures: A Feasibility Study Based on a Case Series - Liu, Jing; Zhang, Li; Qiu, Ru-Xin (Frontiers in Pediatrics, 2022)
Background Fracture is a common birth injury in neonates, and its diagnosis mainly depends on chest X-ray examination, while ultrasound is typically not included in the diagnostic work-up of neonatal fractures.The aim of this study was to investigate the feasibility of using ultrasound to replace X-ray for the diagnosis of fractures in newborns and to determine the ultrasound characteristics of such fractures. Methods Bedside ultrasound with an appropriate probe and scanning angle was performed in 52 newborn infants with suspected fractures based on physical examination findings, and the ultrasound results were compared with the X-ray examination results. Results All 52 infants (100%) showed typical signs of fracture on ultrasound, including 46 cases of clavicle fracture,3 cases of skull fracture,2 cases of rib fracture and 1 case of humerus fracture. Ultrasound was able to detect interrupted cortical continuity, displacement or angulation at the broken end, and callus formation during the recovery period.Chest X-ray examination was performed on 30 patients and identified 96.7% (29/30) of fractures, and the coincidence rate between ultrasound and X-ray was 100%.However,the sensitivity of ultrasound was higher than that of X-ray. Conclusion Ultrasound diagnosis of neonatal fracture is accurate,reliable,simple,and feasible.Therefore,it can replace X-ray examinations for the routine diagnosis of common types of neonatal bone fractures.